Tổng hợp, nghiên cứu cấu trúc và thăm dò hoạt tính sinh học của các phức chất Cu(II), Ni(II) với xitronenlal và menton thiosemicacbazon - Hồng Tuyết và cộng sự, Phan Thị (Vietnam Journal of Chemistry, 2014)
Two new thiosemicarbazones derived from natural aldehyde and ketone, and their nickel(II), copper(II) complexes were synthesized and characterized by IR,UV-VIS, MS and NMR spectroscopies. The results indicate the formation of 1:2 metal to ligand complexes with empirical formulae [CuL2] and [NiL2] (HL: thiosemicarbazone). The Cu(II) and Ni(II) complexes are four coordinate and square planar geometry in which the ligands behave as bidentate chelating agents in the uninegatively charged form. The biological activity of thiosemicacbazones and complexes against the bacteria, fungi and cancer cell have been tested.